Development of a pelvic exenteration service at a tertiary referral centre. Issue 7 (6th March 2018) - Dickfos, Marilla; Tan, Stephanie B. M.; Stevenson, Andrew R. L.; Harris, Craig A.; Esler, Rachel; Peters, Matthew; Taylor, David G.
Abstract : Background: Over one‐third of primary rectal cancers are locally advanced at diagnosis, and local recurrence of rectal cancer occurs at a rate of 3–10% following primary curative resection. Extended resectional surgery, including pelvic exenteration, is the only proven therapy with curative potential in the treatment of these cancers along with many other pelvic malignancies. A microscopically clear resection margin (R0 resection) is the predominant prognostic factor affecting overall and disease‐free survival. The extent and complexity of surgery required to achieve an R0 resection is associated with significant risk of morbidity and mortality. The aim of this paper is to show that pelvic exenterations can be performed with acceptable oncological and safe perioperative results in an appropriately resourced specialist centre. Methods: Data was collected retrospectively for 61 consecutive patients treated between June 2012 and February 2017. This included patient demographics, tumour characteristics, operative, clinical and histological data, length of hospital stay, morbidity and mortality data. Results: A total of 61 patients underwent surgery. Median age was 57 years (range 27–78 years). Median length of stay was 41 days (range 6–288 days). Median operative time was 624 min (range 239–1035 min); 30‐day mortality was 3.3% ( n = 2). Resection rates were 91.5% – R0, 6.8% – R1 and 1.7% – R2 resections. Histologically, 86.9% – adenocarcinomas, 3.3% – squamous cell carcinomas and 9.8% – represented by leiomyosarcoma, melanoma, myxoid chondrosarcoma, non‐neoplastic processes and undifferentiated carcinoma. Conclusion: Our experience confirms that radical resectional pelvic surgery can be safely performed with acceptable results during the establishment phase of a dedicated tertiary service.